The "Odissey" in the Start Place of the Juego de la Oca - Almodóvar García, Javier; del Canto Nieto, José Ramón (Amaltea. Journal of Myth Criticism, 2019)
The trace left by the Odissey in the Western imaginary is inexhaustible. It follows a literary but also iconic tradition. In this article we track down the origin of the "board games" in Greco-Roman Antiquity and their mythical source; its structure and symbolic components are analyzed in order to establish a relationship between the Odyssey and the Juego de la Oca. The method used for this purpose is V. Propp’s analysis of the functions of the popular fairy tale.